Gold-catalyzed intramolecular oxidative cross-coupling of nonactivated arenes. - Hopkinson, M; Tessier, A; Salisbury, A; Giuffredi, G; Combettes, L; Gee, A; Gouverneur, V (2010)
(Chemical Equatation Reprentation An (Au)some coupling! Gold-catalyzed cascade C-O cyclizations of benzyl-substituted allenoate esters followed by intramolecular oxidative C-C cross-coupling involving aryl C-H functionalization were performed with Selectfluor as the oxidant (see scheme). This operationally simple and mild procedure benefits from complete axis-to-center chirality transfer and allows for the preparation of surprisingly uncommon tricyclic motifs. © 2010 Wiley-VCH Verlag GmbH and Co. KGaA.